Analysis of the Economic Viability of the Installation of a Photovoltaic System at Jorge de Abreu Regional Hospital in Sinop-MT - Matheus Holzbach; Carla Carol Silva e Carvalho; Adriana Souza Resende (Renewable Energy and Sustainable Development, 2021)
Brazilian consumers have the possibility to produce their own energy using renewable sources or qualified cogeneration and even provide the surplus for the distribution network of their locality, as determined by the publication of Normative Resolution 482/2012 by the National Electric Energy Agency (ANEEL). In view of this, the use of photovoltaic systems for electricity generation has grown surprisingly, reaching the mark of 8 gigawatts of installed power on Brazilian soil in the year 2021 [1]. In Brazil, public agencies represent 0.1% with 4.7MW installed [1], and in the state of Mato Grosso 0.38% [14]. Thus, aiming at the rise of electricity generation in public buildings, due to the possibility of reducing costs with the electric bill, the present work deals with the dimensioning, budget quotation and economic feasibility analysis regarding the installation of a grid-connected photovoltaic power generation system to meet the energy demands of the Jorge de Abreu Regional Hospital in the city of Sinop, Mato Grosso state, Brazil. Whose, after carrying out the necessary research based on the techniques present in the economic sciences, as Minimum Attractiveness Rate (MRA), Net Present Value (VLP), Internal Rate of Return (IRR) and calculation of Payback. The present work considered a grid-connected solar energy generation system of 585 kW to supply the hospital's average monthly consumption of 93.829 kWh/month. The investment analysis showed that the project for the implementation of the photovoltaic system will have its NPV viable from the 4th year of installation and the Payback (return on investment), observing the monetary corrections, of approximately 4,29 years, thus configuring the system as economic financially.   Received: 25 May 2021 Accepted: 15 July 2021 Published: 10 November 2021